Impact of the COVID-19 Epidemic on the Routine Emergency Services in a Tertiary Hospital, China: A Retrospective Cohort Study. (9th October 2022) - Liang, Lianjing; Zhang, Zhuo; Li, Ping; Weng, Shanshan; Nie, Hu
Abstract: Background: The sudden outbreak of the COVID-19 pandemic has caused tremendous challenges to the medical system. The government and hospitals have taken robust measures to curb the spread of the deadly virus. Its impact on routine medical services is gradually being taken seriously. Objective: To identify the impact of the novel Coronavirus pandemic on emergency department (ED) patient flow and the performance of the routine ED service. Methods: This retrospective cohort study was undertaken in a tertiary public teaching hospital ED in Chengdu, China. ED data of patients were routinely collected to compare demographic, clinical characteristics and outcomes during an 8-week period from January 1, 2019 to February 25, 2020. Data were analyzed with the chi-square statistical test. Results: Over the study periods, there were 31855 and 25244 patients presented to the ED in 2019 and 2020 respectively. During the pandemic period in 2020, the daily number of average ED visits was lower than that in 2019 (430 ± 134.9 versus 572 ± 38.6, P = 0.00), with fewer triage 1&2 cases (145 ± 33.3 versus 178 ± 15.0, P = 0.00). Nevertheless, the mortality increased remarkably during the pandemic period in 2020 (0.2% versus 0.1%, P = 0.009), with higher APACHE II scores (28 versus 19, P = 0.022) and shorter ED elapsed time (0.2 versus 1.4 days, P = 0.016) among these death cases. Conclusions: The COVID-19 pandemic had an evident impact on the patient's behavioral patterns and routine emergency services, which caused higher ED mortality.